Kajian Kesesuaian Wisata dan Daya Dukung Kawasan Wisata Pemandian Alam Tangkahan Taman Nasional Gunung Leuser - Sari, Susi Wanda; Iswahyudi, Iswahyudi; Rosmaiti, Rosmaiti (Medan Resource Center, 2023)
The aim of this study was to identify the types of parasites present in betta fish at Farm Irwan Fisheries in Banda Aceh. The research was conducted from January to February 2022 at Tangkahan Natural Baths, located within Gunung Leuser National Park in North Sumatra Province. The survey method was employed, utilizing scoring analysis derived from field observations. Purposive sampling was applied to select specific sample points intentionally, based on their potential to become tourist attractions. The results indicated that Tangkahan Natural Baths in Gunung Leuser National Park exhibited a high level of suitability as a recreational tourism area, with a suitability index value of 83.65% based on the physical, chemical, and biological parameters of the water. This finding categorizes it as